Photoelectroanalytical Oxygen Detection with Titanate Nanosheet – Platinum Hybrids Immobilised into a Polymer of Intrinsic Microporosity (PIM‐1). Issue 12 (3rd September 2020) - Fan, Bingbing; Zhao, Yuanzhu; Putra, Budi Riza; Harito, Christian; Bavykin, Dmitry; Walsh, Frank C.; Carta, Mariolino; Malpass‐Evans, Richard; McKeown, Neil B.; Marken, Frank
Abstract: The polymer of intrinsic microporosity PIM‐1 is employed to disperse and deposit a Pt@titanate nanosheet photocatalyst film. The resulting microporous films allow electrolyte and oxygen permeation to give conventional oxygen reduction voltammetric responses on glassy carbon or on platinum disk electrodes in the dark. Preliminary data are presented showing that with pulsed light from a blue LED (385 nm) oxygen reduction at the electrode is effectively "switched off". A mechanism is tentatively assigned as photocatalytic depletion of oxygen near the electrode. Photoelectrochemical current responses are observed in aqueous NaOH, NaCl, Na2 HPO4 and shown to be light intensity and oxygen concentration dependent. Electroanalytical applications are suggested. Abstract :